2020
DOI: 10.1371/journal.pone.0237351
|View full text |Cite
|
Sign up to set email alerts
|

Empirical vs. light-use efficiency modelling for estimating carbon fluxes in a mid-succession ecosystem developed on abandoned karst grassland

Abstract: Karst systems represent an important carbon sink worldwide. However, several phenomena such as the CO 2 degassing and the exchange of cave air return a considerable amount of CO 2 to the atmosphere. It is therefore of paramount importance to understand the contribution of the ecosystem to the carbon budget of karst areas. In this study conducted in a midsuccession ecosystem developed on abandoned karst grassland, two types of model were assessed, estimating the gross primary production (GPP) or the net ecosyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
0
5
1
Order By: Relevance
“…After comparing the effects of temperature, moisture, and photosynthetically active radiation on RE and GEE, we found that temperature was the main influencing factor, which is consistent with many studies [ 49 , 50 ]. However, in some plant photosynthesis and respiration models [ 51 , 52 , 53 , 54 ], GEE is mainly calculated based on light and RE is mainly calculated based on temperature, which is different from the results of this paper. This shows that when calculating RE and GEE in models, indicators at different locations may require different weights.…”
Section: Discussioncontrasting
confidence: 68%
“…After comparing the effects of temperature, moisture, and photosynthetically active radiation on RE and GEE, we found that temperature was the main influencing factor, which is consistent with many studies [ 49 , 50 ]. However, in some plant photosynthesis and respiration models [ 51 , 52 , 53 , 54 ], GEE is mainly calculated based on light and RE is mainly calculated based on temperature, which is different from the results of this paper. This shows that when calculating RE and GEE in models, indicators at different locations may require different weights.…”
Section: Discussioncontrasting
confidence: 68%
“…145 The RS environment signicantly boosts the accuracy of the model, especially for production efficiency models such as the LUE models, to analyze the regional carbon ux. 15,47,137,146 Also, these models are reliable sources of regional GPP and NPP in RS carbon ux estimation, given that they provide knowledge on the biotic strata, growth, conditions, etc. These models are dynamically related to RS with the biotic absorbed photosynthetically active radiation (APAR) 15 and fraction of photosynthetically active radiation (fPAR) 48 in estimating the key uxes.…”
Section: Non-destructive Methodsmentioning
confidence: 99%
“…Few models optimize the RS data as parameters in the estimation to reduce the uncertainty in the simulated carbon uxes. 146 Limitations in the RS-based estimation exist in the dataset in terms of atmospheric contamination (cloud cover and reectivity), sensor errors, retrieval algorithm errors, etc., which signicantly increase the uncertainty. 15 These data errors pertain to the data sources, such as the errors in data acquisition, processing, and validation.…”
Section: Non-destructive Methodsmentioning
confidence: 99%
See 2 more Smart Citations